REHABILITATION MEASURES IN THE PALLIATIVE DEPARTMENT, CLINICAL CASE OF A PATIENT AFTER COVID-19 - Homola, Alona; Tsiganenko, Alexander (Scientific Journal of Polonia University, 2023)
Covid-19 is an infectious disease caused by the SARS-CoV-2 virus. It is a pandemic acute respiratory illness. The virus spreads and is transmitted through the mouth or nose drops of an infected person, while talking, coughing, sneezing, and more likely in crowded places. By breathing in respiratory droplets or small particles, a healthy person has a high risk of infection. The disease is experienced in different ways, from the onset of slight malaise to recovery, and from a severe course of the disease, the consequences arising from the viral infection, which do not do without the help of doctors. Objective. To study a clinical case of a patient after Covid-19. Material of investigation was the clinical case of a 61-year-old woman, admitted after 40 days of resuscitation to the Palliative Department, Kyiv City Clinical Hospital № 6. Methods of investigation: history of the patient after Covid-19, collection of anamnesis, laboratory and clinical methods of examination. The multidisciplinary team headed by the head of the palliative department was created. We used all possible rehabilitative measures to achieve the set objectives successfully. Results. The patient received the full range of diagnostic and rehabilitative measures. After the end of treatment and rehabilitation measures, the follow-up observation by the family doctor was recommended, it testifies to the successful improvement of the patient’s functional state. Conclusion. The article presents my own experience, and introduction of the patient after Covid-19 in the Palliative Department, Kyiv City Clinical Hospital № 6. Individual approach and cohesion of the multidisciplinary team help to fulfill the patient’s needs to the fullest extent. The important practical questions of rehabilitation measures for patients with the consequences of Covid-19 are considered.